2014
DOI: 10.1016/j.ceramint.2014.04.023
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mechanical activation on the electrical properties of Ba0.77Sr0.23TiO3 ceramics

Abstract: Ferroelectric barium strontium titanate (Ba 0.77 Sr 0.23 TiO 3 ), BST, was prepared by solidstate reactions using as the starting compounds the powders of barium carbonate (BaCO 3 ), strontium carbonate (SrCO 3 ) and titanium dioxide (TiO 2 -anatase). Non-activated mixtures and mixtures mechanically activated in a high-energy planetary ball mill (0, 5, 10, 20, 40, 80 and 120 minutes) were sintered at 1100, 1200, 1300 and 1400 °C for 2 hours in air atmosphere.Defects and the effect of the beginning of the sinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Herein we present a study of the influence of the chemical composition of BST powder on its microstructural properties and sintering kinetics, as a part of an a broader study of the influence of composition and microstructural parameters on sintering behavior and functional properties of BST [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Herein we present a study of the influence of the chemical composition of BST powder on its microstructural properties and sintering kinetics, as a part of an a broader study of the influence of composition and microstructural parameters on sintering behavior and functional properties of BST [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Fe (110) and BaTiO 3 (100) planes are a relatively close match in terms of lattice constants (a mismatch is only about 1.4%), which allows layer-by-layer epitaxial growth of Fe/BaTiO 3 multi-layers with no misfit dislocations. Mechanical activation is a wellestablished preparation route for various titanate based based electroceramics [11][12][13][14][15][16][17]. At higher Fe:Ba ratios, barium hexaferrite BaFe 12 O 19 , an M type hexagonal ferrite, is usually formed, which, like other ferrite materials, has been used as a permanent magnet for electronic and microwave applications [18][19][20][21][22], due to its large uniaxial magnetic anisotropy [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the influence of thermal treatments for the Fe-implanted BTO films was followed with decrease of coercivity and enhancement of magnetization [17,18]. Mechanical activation is well established preparation route for barium-titanate [19] and magnesium titanate (MTO) [20] based electroceramics.…”
Section: Introductionmentioning
confidence: 99%